مقارنة بين النباتين الدالينIpomoea setosa وIpomoea nil لجهة استخدامها في الكشف عن فيروس التبرقش الريشي على نباتات البطاطا الحلوة - عاقل, إنصاف; درويش, يولا; إسماعيل, عماد; الشعبي, صلاح (Latakia University Journal -Biological Sciences Series, 2019)
أجريت هذه الدراسة للمقارنة بين النباتين الدالين Ipomoea setosa و Ipomoea nil تجاه عزلات محلية مختلفة من فيروس التبرقش الريشي على البطاطا الحلوة Sweet Potato Feathery Mottle Virus في الساحل السوري. أظهرت النتائج أن نسبة أعراض الإصابة الظاهرية على النبات الدال I. setosa المزروع في الحقل وصلت إلى أكثر من96 %، أما المعدى بالتطعيم والمحتفظ به داخل الأقفاص المانعة لدخول الحشرات فقد وصلت إلى 95%، بينما وصلت نسبة أعراض الإصابة الظاهرية على النبات الدال I.nil المزروع في الحقل المفتوح إلى 50% و المعدى بالتطعيم داخل الأقفاص المانعة لدخول الحشرات إلى 62.5 %. كما بينت النتائج التفضيل الغذائي في ظروف الزراعة الحقلية على النبات الدال I. Setosa من قبل حشرات المن الناقلة للفيروس. أكدت الدراسة أهمية النبات الدال I. setosa في إظهار التباين في أعراض الإصابة الظاهرية تجاه العزلات المختلفة للفيروس، وتفوقه في الحساسية على النبات الدال I. nil، وبالتالي إمكانية استخدامه لاحقاً بوصفها عائلاً أكثر ملائمة تحت الظروف المحلية لمضاعفة الفيروس، ودراسات أخرى. This study was conducted in order to compare between two indicator plants Ipomoea setosa & Ipomoea nil and to identify their sensitivity against sweet potato feathery mottle virus on the Syrian coast. Results showed that different reactions on the same indicator plants I. setosa and I. nil were observed, revealing different virus symptoms when these plants were grafted by virus-infected scion, or planted in the fields. The highest ratios of virus symptoms and virus infection on I. setosa were 96% in the fields and 95% under laboratory conditions; whereas those on I. nil were 50% in the fields and 62.5% in laboratory. It has been found that I. setosa was of more performance when these two indicator plants were grafted by virus-infected scion, or planted together in the field beside infected plants. I. setosa could be used as an indicator plant for sweet potato feathery mottle virus propagation and other studies.